Sociocultural Determinants of Attitudes Toward Domestic Violence Among Women and Men in Afghanistan: Evidence from Afghanistan Demographic and Health Survey 2015 - Akbary, Mohammad Fazel (Journal of interpersonal violence, 2022)
Domestic violence (DV), also commonly referred to as intimate partner violence or spousal abuse, is a global public health issue that affects the physical, psychological, sexual, and reproductive health of women. We examined the sociocultural factors associated with the attitude toward DV perpetrated against women in Afghanistan. We used data from the 2015 Afghanistan Demographic and Health Survey, consisting of an ever-married sample of 29,461 women and 10,760 men aged 15 to 49 years. Our dependent variable, attitude toward DV, was determined from responses on acceptance of wife-beating in five scenarios, and the group of socio cultural factors was selected based on evidence from previous studies. Our main analytical method was logistic regression, using the survey design. Our findings indicated that factors such as an increase in years of education and living in a wealthier household reduce the likelihood of acceptance of DV among men and women. Ethnicity was also associated with the attitude toward DV, but the magnitude varied across ethnic groups and gender. Furthermore, an increase in age and living in the urban area were associated with nonjustification of DV among women, but not among men. On the other hand, frequent exposure to the media increases the likelihood of acceptance of DV among men, but not for women. The result of the present study suggests that there are economic, social, and cultural aspects to the attitude toward DV among men and women in Afghanistan. Therefore, policies designed at changing the socio cultural perception of the people are of importance in other to bring about a change in attitude, and even combat the prevalence of DV.